Reaksi Investor Pada Peristiwa Pengumuman Kabinet Indonesia Maju - Sudarmo Sudarmo; Fidiana Fidiana; Kurnia Kurnia (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
This study aimed to explain investors’ reaction in the Indonesian capital market to the Announcement of the Jokowi and Ma’ruf Amin’s Cabinet of Indonesia Maju. This study investigated companies listed on the LQ 45 Index of the Indonesia Stock Exchange in 2019 as its population. Moreover, the purposive sampling method was to determine the sample that included 38 companies. This study collected data using documentation techniques within fifteen days. The periods were seven days before the Indonesia Maju Cabinet’s Announcement and seven days after the Announcement, from 14 October 2019 to 01 November 2019. The testing approach was an event study approach. The analysis technique was to test the signifi-cance level of the average abnormal return, and moderate trading volume activity is the paired sample t-test. The results indicated no difference in average abnormal return before and after the Indonesia Maju Cabinet’s Announcement. There was no difference in moderate trading volume activity before and after the Indonesia Maju Cabinet’s Announcement. In other words, there was a less positive reaction from investors around the Indonesia Maju Cabinet’s information